1H Quantitative NMR analyses of β-asarone and related compounds for quality control of Acorus rhizome herbal drugs in terms of the effects of their constituents on in vitro acetylcholine esterase activity. Issue 5 (4th May 2019) - Lynn, Nwe Haymar; Linn, Thein Zaw; Yanmei, Cui; Shimozu, Yuuki; Taniguchi, Shoko; Hatano, Tsutomu
ABSTRACT: We used quantitative nuclear magnetic resonance analyses to measure the contents of major constituents of Acorus rhizome materials used as herbal drugs. The inhibitory effects of crude n -hexane extracts and their individual constituents on in vitro acetylcholine esterase activity were evaluated. The crude extracts had unexpectedly weak inhibitory effects (46–64% inhibition at 1.0 mg/mL), despite the high content (46–64%) of β-asarone, which independently had a potent effect (IC50 2.9 µM [0.61 µg/mL]). Further investigation revealed participation of eudesmin A, a lignan constituent, in the suppression of the inhibitory effect of β-asarone. Graphical abstract: : 1 H Quantitative NMR analyses of β-asarone and related compounds for quality control of Acorus rhizome herbal drugs in terms of the effects of their constituents on in vitro acetylcholine esterase activity